Acute Stress and an Electrolyte- Imbalanced Diet, but Not Chronic Hypoxia, Increase Oxidative Stress and Hamper Innate Immune Status in a Rainbow Trout (Oncorhynchus mykiss) Isogenic Line - Magnoni, Leonardo J.; Novais, Sara C.; Eding, Ep; Leguen, Isabelle; Lemos, Marco F. L.; Ozório, Rodrigo O. A.; Geurden, Inge; Prunet, Patrick; Schrama, Johan W. (Frontiers in Physiology, 2019)
Fish may be exposed to sub-optimal rearing conditions, which generate a stress response if full adaptation is not displayed. However, our current knowledge of several coexisting factors that may give rise to a stress response is limited, in particular when both chronic and acute stressors are involved. This study investigates changes in metabolic parameters, oxidative stress and innate immune markers in rainbow trout (Oncorhynchus mykiss) exposed to a combination of dietary (electrolyte-balanced or imbalanced diet, DEB-200 and 700 mEq Kg-1, respectively) and environmental (normoxia or hypoxia, 7.9 and 4.5 mg O2 L-1, respectively) challenges for 49 days. At the end of this period, fish were subsequently subjected to an acute stressor (2 min of handling/confinement) or maintained under the corresponding controls. Feeding trout an electrolyte-imbalanced diet produced a reduction in blood pH, as well as increases in cortisol levels, HSI and total energy content in liver. The ratio between the lactate dehydrogenase (LDH) and isocitrate dehydrogenase (IDH) activities decreased in the liver of trout fed the DEB-700 diet, but increased in the heart, suggesting a different modulation of metabolic capacity by the dietary challenge. Markers of oxidative stress related to the glutathione system in the liver of trout were altered when fed the DEB-700 diet. The dietary challenge was also associated with a decrease in the alternative complement pathway activity (ACH50) in plasma, suggesting an impaired innate immune status in that group. Trout subjected to the acute stressor displayed reduced blood pH, higher plasma cortisol levels as well as increased levels of metabolic markers associated with oxidative stress in the liver. An interaction between diet and acute stressor was detected for oxidative stress markers in the liver, showing that the dietary imbalance impairs the response of rainbow trout to handling/confinement. However, trout reared under chronic hypoxia only displayed changes in parameters related to energy use in both liver and heart. Taken together, these results suggest that trout displays an adapta-tive response to chronic hypoxia. Conversely, the dietary challenge profoundly affected fish homeostasis, resulting in an impaired physiological response leading to stress, which then placed constraints on a subsequent acute challenge.